Bladder cancer risk in users of selected drugs for cardiovascular disease prevention. Issue 2 (March 2019) - Guercio, Valentina; Turati, Federica; Bosetti, Cristina; Polesel, Jerry; Serraino, Diego; Montella, Maurizio; Libra, Massimo; Galfano, Antonio; La Vecchia, Carlo; Tavani, Alessandra
Abstract : The aim of this study was to investigate the relation between bladder cancer risk and the use of selected drugs for cardiovascular disease (CVD) prevention, such as aspirin, statins, and calcium channel blockers (CCBs). We analyzed data from a multicentric case–control study carried out in Italy between 2003 and 2014, including 690 bladder cancer cases and 665 hospital controls. Odds ratios (ORs) of bladder cancer and corresponding 95% confidence intervals (CIs) were estimated using unconditional multiple logistic regression models. The ORs for bladder cancer were 1.21 (95% CI: 0.87–1.68) for regular use of aspirin, 0.72 (95% CI: 0.54–0.97) for use of any CCBs, and 1.32 (95% CI: 0.87–1.99) for use of any statins. A slight inverse association was found with duration of use of CCBs, whereas no consistent association was found with duration of use, age at first use, and frequency for aspirin and statin use, or with indication of use for aspirin (as an analgesic or, for CVD prevention). No significant association was found for various combinations of drugs or for all drugs combined (OR=1.23, 95% CI: 0.31–4.85). Our data indicate the lack of a relevant association between the use of selected drugs for CVD prevention and bladder cancer risk, although suggest a potential favorable role for CCBs.